Be the opportunity: the heart and soul of corporate social responsibility. (1st February 2019) - Chin, Motthida
Abstract : Companies engage in corporate social responsibility (CSR) as a way to strengthen their business objectives and demonstrate their commitment towards ethical labour practices, safe working conditions and equitable trade. There are many methods to achieve these objectives, and success is often expressed quantitatively. Throughout my twenty years of CSR practice and counsel, however, I have found that while the quantitative success is important for all parties involved to co-operate willingly, to meet objectives, the heart and soul of effective CSR is essentially about relationship building that fuels opportunities for workers, in particular for women and girls in the workplace and in their communities.